Locus of Control and Savings - Deborah A. Cobb-Clark; Sonja C. Kassenböhmer; Mathias Sinning (Institute for the Study of Labor (IZA), 2013)
This paper analyzes the relationship between individuals' locus of control and their savings behavior, i.e. wealth accumulation, savings rates, and portfolio choices. Locus of control is a psychological concept that captures individuals' beliefs about the controllability of life events and is a key component of self-control. We find that households with an internal reference person save more both in terms of levels and as a percentage of their permanent incomes. Although the locus-of-control gap in savings rates is largest among rich households, the gap in wealth accumulation is particularly large for poor households. Finally, households with an internal reference person and average net worth hold significantly less financial wealth, but significantly more pension wealth, than otherwise similar households with an external reference person.
Keywords: G02; G11; I31; R21; 330; non-cognitive skills; locus of control; wealth accumulation; asset portfolios; savings